Business Operators' Liability for Consumer Losses due to Non-Standard Medical Devices: Civil Law Analysis - Ratih Pratiwi Syurkawi (Jurnal Justiciabelen, 2025)
The civil liability of business operators in cases where consumers suffer losses due to the circulation of non-standard medical devices. The main problem addressed is the lack of legal certainty and consumer protection when defective or unsafe medical products enter the market. The novelty of this research lies in identifying business operators’ responsibility not only through contractual liability but also through extra-contractual liability under tort law and consumer protection regulations. Using a normative juridical research method with statute, conceptual, and case approaches, this research finds that business operators are legally accountable when failing to meet safety and quality standards of medical devices. Such violations constitute breaches of contract as well as unlawful acts that entitle consumers to claim compensation. The conclusion suggests the necessity of reinforcing regulatory oversight and adopting strict liability principles to strengthen consumer rights and minimize risks arising from non-standard medical devices.